Strategi Pemasaran Usaha Ayam Petelur Pak Muhib Melalui Pembuatan Logo, Merk, Kemasan Dan Digitalisasi Dalam Meningkatkan Penjualan - Fina Karima; Bintis Ti’anatud Diniati (CV. Armas Suan Sejahtera, 2026)
The micro sector dominates the Micro, Small, and Medium Enterprises (MSMEs) landscape in Bojonegoro, facing structural gaps and high market competition. This empowerment activity aimed to formulate and implement an integrated marketing strategy for Pak Muhib’s laying-hen business in Ngujo Village, Kalitidu District, Bojonegoro Regency, to build competitive advantage amidst fluctuating egg prices. Using Participatory Action Research (PAR) within a qualitative approach, data were gathered through observation, in-depth interviews, and documentation, then analyzed using thematic analysis. The intervention steps included problem identification, co-creation of logos and brands, packaging improvement, and gradual digitalization using WhatsApp. The results demonstrated positive marketing improvements, where egg sales steadily rose to 32 kg/month, recovering the monthly turnover to IDR 832,000 in May 2026 despite low market prices. Socially, it fostered a new marketing consciousness and established the partner as a local leader for surrounding farmers. The main strength of this program was its participatory approach that drove genuine behavioral transformation. However, it was constrained by limited digital literacy and the partner's operational time constraints in managing the farm. Future development should focus on sustainable assistance regarding business time management and introducing automated digital ordering tools to ensure long-term economic independence.